2022
DOI: 10.1002/viw.20210009
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between polymeric nanoparticles and different buffers as investigated by zeta potential measurements and molecular dynamics simulations

Abstract: Zeta potential is an essential surface parameter in the characterization of nanoparticles, determined at the interface of loosely bound ions (diffuse layer) at the nanoparticle surface and free ions in solution. The ionic concentration and pH of the solution are known to, by definition, influence the composition of the diffuse layer and zeta potential accordingly. Thus, to fix the solution's pH for valid zeta potential measurements, buffers are frequently used. However, an issue that remains largely neglected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…The thin dried film in the flasks was hydrated with salt-free HEPES buffer, which contains free carboxylic acid groups capable of neutralizing cationic amine groups of dequalinium or forming an electrostatic coating layer on the outer surface of the dequalinium based particle. The statistical analysis revealed a decrease in anionic values with increasing amounts of When nanoparticle-buffer ratio 0.002, its charge turns into -14.2 mV [39]. In our study, dequalinium chloride was used as a cationic lipid.…”
Section: Dqasome Preparation and Characterizationmentioning
confidence: 60%
“…The thin dried film in the flasks was hydrated with salt-free HEPES buffer, which contains free carboxylic acid groups capable of neutralizing cationic amine groups of dequalinium or forming an electrostatic coating layer on the outer surface of the dequalinium based particle. The statistical analysis revealed a decrease in anionic values with increasing amounts of When nanoparticle-buffer ratio 0.002, its charge turns into -14.2 mV [39]. In our study, dequalinium chloride was used as a cationic lipid.…”
Section: Dqasome Preparation and Characterizationmentioning
confidence: 60%
“…TEM image analysis revealed that the formed NPs are spherical with a size range of 150 ± 30 nm. The size difference between DLS and TEM was due to different working principles as DLS is based on light-scattering hydrodynamic data, which can be easily influenced by particle agglomeration . On the contrary, TEM imaging analysis was performed after the sample was dried completely, resulting in a smaller size.…”
Section: Resultsmentioning
confidence: 99%
“…Because the anthocyanins at neutral pH convey minor charges, changes in zeta potential were probably due to hydrogen bonding interactions between RCE, CNC, and NFC with increased concentration of the RCE in suspensions. Inam et al (2022) reported that noncovalent interactions between polymeric nanoparticles and 2-[4-(2-hydroxyethyl)piperazin-1yl]ethanesulfonic acid (HEPES), as a zwitterionic molecule, play a crucial role in changing the zeta potential values. According to their report, hydrogen bonding interactions can suppress the zeta potential value of polymeric nanoparticles.…”
Section: Suspension Structure and Rheologymentioning
confidence: 99%